PEMANFATAAN KOLEKSI ANAK DI PUSTAKALANA CHILDREN’S LIBRARY UNTUK KEGIATAN MEMBACA NYARING - Fadhilah Luthfi Afifatunnisa; Agus Rusmana; Yunus Winoto (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2023)
In a child's learning process, the read-aloud method is a simple literacy practice that has a big impact. Pustakalana Children's Library created a program that focuses on reading aloud. A quality children's reading collection is needed to help children increase their interest in reading. Likewise, the role of librarians and parents who read aloud the collection. This study aims to look at the phenomenon of utilizing children's collections at Pustakalana for reading-aloud activities. The research method used is a qualitative case study method with data collection techniques through observation, interviews, and documentation. Based on the results of the study, shows that reading is very important in children's lives because reading activities can form imagination patterns, and gain knowledge to activate children's creativity. Doing the read-aloud method to children can accelerate the development of their way of thinking to be more critical. Pustakalana facilitates read-aloud activities to improve children's reading and creativity through papercraft-making activities. However, the role of parents as role models for children in the family environment is also very important. Parents should set a good example by reading books out loud to their children. Reading regularly is the key to the success of this reading method.